2019
DOI: 10.1001/jamanetworkopen.2019.0185
|View full text |Cite
|
Sign up to set email alerts
|

Association of Long-term Use of Low-Dose Aspirin as Chemoprevention With Risk of Lung Cancer

Abstract: Key Points Question Is long-term use of low-dose aspirin associated with reduced risk of lung cancer, and if so, which populations may derive the greatest benefit? Findings This cohort study using data from 12 969 400 participants in the Korean National Health Information Database found that the use of low-dose aspirin for more than 5 years was associated with a modest risk reduction of incident lung cancer, with the strongest association observed among eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 42 publications
(45 reference statements)
2
29
0
1
Order By: Relevance
“…The selection of LD ASA, the dosing schedules and duration of intervention may have led to the minimal effects on the pre-selected gene-expression signatures. Although a body of data supports the development of LD ASA in lung cancer chemoprevention (32,33), it is possible that regular-strength ASA might have yielded more robust modulation of the gene signatures in the anti-carcinogenic direction. An additional arm of regular-strength ASA would have strengthened the study by addressing doseresponse in modulating risk of tobacco exposure and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of LD ASA, the dosing schedules and duration of intervention may have led to the minimal effects on the pre-selected gene-expression signatures. Although a body of data supports the development of LD ASA in lung cancer chemoprevention (32,33), it is possible that regular-strength ASA might have yielded more robust modulation of the gene signatures in the anti-carcinogenic direction. An additional arm of regular-strength ASA would have strengthened the study by addressing doseresponse in modulating risk of tobacco exposure and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 49 These results are consistent with those observed from a study on about 10 000 cancer samples across 21 cancer types in The Cancer Genome Atlas. 50 Both studies are based on 15 Buffa signatures instead of low-oxygen level as a direct indicator because it is not contained in the databases. Moreover, higher hypoxic signaling and hypoxia-associated genes tend to occur in tumors with higher diversity and are correlated with a poorer overall survival (OS) and progression-free survival (PFS).…”
Section: Hallmarks Of Tmementioning
confidence: 99%
“…In a study on the role of aspirin in reducing cancer risk, various doses, frequencies, and duration have been selected, such as the following: ≥975 mg/w for more than 5 years, 177 ≥150 mg/d for more than 1 year, 178 ≥325 mg/d for more than 5 years, 179 600 mg/d for a mean of 25 months, 180 100 mg/d for at least 104 d/y. 50 Similarly, when assessing aspirin’s role in combination with other treatment modalities, these indices should also be carefully selected. Gastrointestinal bleeding is always a concern when using aspirin.…”
Section: Conventional Drugs With New Use: Candidate For Tme-targetingmentioning
confidence: 99%
“…65 A large retrospective study including more than 10 million people in South Korea confirmed that long-term use of low-dose aspirin was associated with a decreased risk of lung cancer. 66 Recognition of the tumorpromoting effects of platelets emphasizes the role of antiplatelet therapy in the prevention and treatment of cancer. Nevertheless, identifying cancer patients who will benefit from antiplatelet therapy is still an important issue.…”
Section: Discussionmentioning
confidence: 99%